PEMIKIRAN ISLAM DAN SAINS - Suci Amalia; Nabila Rahmayani; Muhammad Wahyudi (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2022)
The conflict (rivalence) between religion and science covers all fields; both natural science and social science. Unlike before, today there is no longer a religion that opposes a development that has taken place in the field of science. However, it must also be acknowledged that religious opposition to the development of social sciences can still be felt. The objective is to find out about islamic and western science discourse, to find out how islamic science spread to the latin west. the new discourse that science is value-free, in the sense that it is neutral or not influenced by beliefs, appears along with the development of modern science (western science) today. historically, the trauma of western society to the history of their religion, which restrained and liberated science from religious life, was the beginning of the science that is currently developing. while science which develops against religion is considered to be contrary to religion, religion is only known as doctrine.